Foldamers with unusual structural architecture from spirobi(indane) building blocks - Kendhale, Amol M.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
This communication demonstrates the utility of inherently rigid building blocks such as 1,1'-spirobi(indane) for generating conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.